Step by step trasvaginal ultrasound - Dastir, Kakoli (New Delhi : Japee Brothers Medical Publishers, 2015)
Primarily designed to make transvaginal ultrasound more easy and understandable to the junior doctors and students. - Includes schematic diagrams of al the ultrasonography plates to make it more interesting and needful in day-to-day practice. - Incorporates 19 chapters in all consisting of focusing pelvic organs; ultrasound anatomy of uterus, cervix and ovaries.
.
Contents 1. Introduction 2. Focussing pelvic organs 3. Ultrasound anatomy of uterus, cervix and ovaries 4. Uterine anomaly 5. TVUS in locating itrauterine contraceptive device y otros más
Keywords: ULTRASONIDO; OVARIO -- ENFERMEDADES -- DIAGNÓSTICO